Quantitative Real-Time Polymerase Chain Reaction: Methodical Analysis and Mathematical Model - Wilkening, Stefan (The Association of Biomolecular Resource Facilities, 2004)
Real-time polymerase chain reaction was established for 16 genes using the LightCycler system to evaluate gene expression in human hepatocytes. During the experiments a large set of data has been obtained. These data have now been evaluated with respect to template stability, accuracy of melting curve analysis, and reproducibility. In addition, the statistical evaluation of the efficiencies of all 16 polymerase chain reactions led to a new mathematical model. To examine template stability, the degradation of mRNA and cDNA was determined at different temperatures. Surprisingly, cDNA, which was obtained by first-strand synthesis, appeared to degrade significantly faster than the respective mRNA. Melting curve analysis is a fast and sensitive method to check for polymerase chain reaction specificity. However, we show that two transcription variants of the glutathione S-transferase 1 gene, with over 100 bp length difference, could not be distinguished by this method. Furthermore, an equation was set up describing the correlation between polymerase chain reaction efficiency and crossing point. This equation can be used to estimate the number of template molecules without having a standard of known concentration. Finally, experimental reproducibility of the real-time polymerase chain reaction was defined.